Answer:
[tex]\boxed{4x^{2} - 48x + 144}[/tex]
Step-by-step explanation:
Given expression:
To simplify the expression, we will use the formula (a - b)² = a² - 2ab + b².
[Where "a and b" are the first and second term in (a - b)²]
[tex]\rightarrowtail (2x - 12)^{2}[/tex]
In this case, the first term of (2x - 12)² is "2x" and the second term is "12".
[tex]\rightarrowtail (2x)^{2} - 2(2x)(12) + (12)^{2} \ \ \ \ \ \ \ \ \ \ \ \ \ \ [\small\text{First term = a = 2x; Second term = b = 12]}[/tex]
Now, simplify the expression.
[tex]\rightarrowtail (2x)^{2} - 2(2x)(12) + (12)^{2}[/tex]
[tex]\rightarrowtail (2x)(2x) - (4x)(12) + (12)(12)[/tex]
[tex]\rightarrowtail \boxed{4x^{2} - 48x + 144}[/tex]